DIVERSIDADE DE PEIXES EM MICROBACIAS DO ALTO RIO PARANÁ, MATO GROSSO DO SUL - NEVES, Gabriela Ribeiro; CÓRDOVA JÚNIOR, Renner Fernando da Silva; PINHO, Henrique Ledo Lopes; MINILLO, Alessandro; SÚAREZ, Yzel Rondon (ANAIS DO ENIC, 2024)
-